2012
DOI: 10.1021/jp307408u
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Single Transition-Metal Atom Absorbed Graphdiyne and Graphyne Sheet from DFT+U Calculations

Abstract: The electronic and magnetic properties of single 3d transition-metal(TM) atom (V, Cr, Mn, Fe, Co, and Ni) adsorbed graphdiyne (GDY) and graphyne (GY) are systematically studied using first-principles calculations within the density functional framework. We find that the adsorption of TM atom not only efficiently modulates the electronic structures of GDY/GY system, but also introduces excellent magnetic properties, such as half-metal and spin-select half-semiconductor. Such modulation originates from the charg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
174
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(195 citation statements)
references
References 51 publications
16
174
1
Order By: Relevance
“…The control of the electronic properties with adatoms has been considered in Refs. [18][19][20][21][22], which is particularly important in light of inducing topological properties in graphyne-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The control of the electronic properties with adatoms has been considered in Refs. [18][19][20][21][22], which is particularly important in light of inducing topological properties in graphyne-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Subsequent studies suggest that these materials have attractive electronic properties. [29][30][31][32][33][34][35] L. D. Pan et al reported that graphyne nanoribbons are semiconductors with band gaps similar to silicon. 31 A key property of graphyne are the larger rings, compared with the six-member rings in graphene, making it possible to introduce atoms in the same plane as the defect-free carbon sheet.…”
mentioning
confidence: 99%
“…A dilute concentration of select TM atoms at interstitial positions in graphyne has been found to induce half-metallicity. 34,35 J. He et al studied the geometric structures and electronic properties of one dimensional TM nanowires on graphyne.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is desirable to find a material with both large hole and electron mobilities, for ease of fabrication in electronic industry. Previous works focused mainly on γ-graphdiyne [4,5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and a few focused on α-graphdiyne [29][30][31]. However, there should be other types of graphdiynes that also have two acetylenic linkages (diyne).…”
Section: Introductionmentioning
confidence: 99%